The return of behaviourist epistemology: A review of learning outcomes studies. (November 2017) - Murtonen, Mari; Gruber, Hans; Lehtinen, Erno
Abstract: Learning outcomes as a concept has encountered a revival since the beginning of the Bologna process in 1999. The concept itself has a longer history with its roots in the behaviourist tradition of the 1960s. The goal of this review is to study how the historical roots of learning outcomes are noted in current research articles since the launch of the Bologna process and whether the concept of learning outcomes is used critically or uncritically. The review of 90 articles shows that the behaviourist tradition is still evident in the 21st century research with 29% of the articles directly and 11% indirectly referring uncritically to the respective publications or to the behaviourist epistemology. Only a minority of the articles, i.e. 8%, was found to be critical towards the behaviourist meaning of learning outcomes. Highlights: Behaviourist tradition is evident in the 21st century learning outcomes studies. 40% of the articles referred uncritically to the behaviouristic epistemology. Only 8% of the articles were critical towards the behaviourist tradition.